Effect of Wheat and Barley Malt Addition on the Quality of the Baking Blend and Wheat Bread - Justyna Belcar; Joanna Kaszuba; Józef Gorzelany (Polish Journal of Food and Nutrition Sciences)
Wheat grain obtained from agricultural overproduction is stored for a long time in grain warehouses, which reduces its baking value. The aim of this study was to use barley and wheat malt flours as additives to flours obtained from grain of different wheat varieties stored for 12 months under optimal conditions, to improve their baking properties. The addition of barley malt flour at a mean rate of 0.5% or wheat malt flour at a mean rate of 0.7% reduced the time needed for the wheat gel to reach its maximum viscosity by 67.2%, compared to the control sample (without malt flour added). Bread made of flour blends with malt flours added was characterised by a higher loaf volume and specific volume as well as darker crust and crumb. The addition of malt flours also led to significantly reduced hardness, gumminess, and chewiness of bread crumb. The study demonstrated that it is possible to effectively use long-stored wheat grains for bread making applying wheat malt flour or barley malt flour as enhancers.